The Interplay of Organizational Culture, Knowledge Management System, and Learning Evaluation in Improving English Language Skills: A Mixed-Method Study in Indonesian Pesantrens - Ma’arif, Samsul; Fathoni , AB. Musyafa; Suyudi, Suyudi; Yudi, Usman; Muna, Naily El (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study examines the interaction among organizational culture, knowledge management, and learning evaluation in improving English language competence in pesantrens in East Java, using a sequential exploratory mixed-methods design. Qualitative data were collected through interviews, observations, and focus group discussions with pesantren leaders, teachers, and students to identify context-specific dimensions of organizational culture, knowledge management practices, and evaluation systems, which subsequently informed the development of a quantitative instrument administered to 306 respondents across three pesantren. Quantitative analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) indicates that learning evaluation exerts the strongest positive influence on English language competence, underscoring the role of continuous assessment, feedback, and follow-up actions in shaping learning outcomes. Organizational culture also shows a positive contribution by fostering discipline, language habituation, and collective responsibility. In contrast, knowledge management demonstrates a negative relationship with English language competence, reflecting partial implementation, limited technological integration, and fragmented knowledge-sharing practices, as corroborated by qualitative findings. These results highlight the importance of aligning organizational culture, evaluation practices, and context-sensitive knowledge management to enhance English language learning in pesantren while maintaining their core educational values.